2021
DOI: 10.1242/dev.193755
|View full text |Cite
|
Sign up to set email alerts
|

Symmetry and fluctuation of cell movements in neural crest-derived facial mesenchyme

Abstract: In the face, symmetry is established when bilateral streams of neural crest cells leave the neural tube at the same time, follow identical migration routes and then give rise to the facial prominences. However developmental instability exists, particularly surrounding the steps of lip fusion. The causes of instability are unknown but inability to cope with developmental fluctuations are a likely cause of congenital malformations such as non-syndromic orofacial clefts. Here, we tracked cell movements over time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 81 publications
0
10
0
Order By: Relevance
“…4 Inhibition of the proliferation and migration of palatal mesenchymal cells leads to the short development of palatal processes and the failure of palatal processes to connect, resulting in the formation of cleft palate. 5 Moreover, the degeneration or apoptosis of crest epithelial cells in the palatal process, and the inhibition of epithelial-mesenchymal transition (EMT) can also lead to the fusion obstacle of palatal process and the formation of cleft palate. Recent studies reported that microRNAs (miRNAs) are key factors in both normal palatogenesis and cleft palate formation.…”
Section: Introductionmentioning
confidence: 99%
“…4 Inhibition of the proliferation and migration of palatal mesenchymal cells leads to the short development of palatal processes and the failure of palatal processes to connect, resulting in the formation of cleft palate. 5 Moreover, the degeneration or apoptosis of crest epithelial cells in the palatal process, and the inhibition of epithelial-mesenchymal transition (EMT) can also lead to the fusion obstacle of palatal process and the formation of cleft palate. Recent studies reported that microRNAs (miRNAs) are key factors in both normal palatogenesis and cleft palate formation.…”
Section: Introductionmentioning
confidence: 99%
“…This fact is explained, among other things, by a dominant growth potential of the skull and brain on the right side of the face or a greater expression of emotions on the left side of the face [8]. It has been also speculated that neural crest cell migration during fetal growth happens earlier on the right side and tends to be delayed on the left side [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…This fact is explained, among other things, by a dominant growth potential of skull and brain on the right side of the face or a greater expression of emotions on the side of the face [8]. It has been also speculated that neural crest cell migration during fe growth happens earlier on the right side and tends to be delayed on the left side [9,10] (a) (b) Despite the dominance of genetic factors, the mandible's development is sensitive to the influence of modifying en ronmental factors [11,12], such as diet, functioning/loads exerted on the stomatognathic system, size and type of o Despite the dominance of genetic factors, the mandible's development is sensitive to the influence of modifying environmental factors [11,12], such as diet, functioning/loads exerted on the stomatognathic system, size and type of occlusion, work of muscles and muscular tone (including masseter muscles, suprahyoid and infrahyoid muscles, temporal and pterygoid muscles). The most significant factors modifying the development of the stomatognathic system are pathological conditions and dysfunctions of the masticatory organ.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…LR: For me, luckily not as many frustrations as with other projects I've done! I think the biggest challenge was how to interpret what Composite figure of the key experimental data in the paper; for more details, see the full manuscript (Danescu et al, 2021).…”
mentioning
confidence: 99%